Biases in construction project dispute resolution. Issue 2 (18th March 2019) - Cheung, Sai On; Li, Keyao
Abstract : Purpose: This study aims to propose a framework of bias in construction project dispute resolution (CPDR hereafter). Design/methodology/approach: With reference to the literatures on effects of bias, manifestations of bias in CPDR were developed. Based on data obtained from construction professionals about their frequency of having these bias manifestations, the underlying constructs of biased behaviors were explored by a principal component factor analysis. A confirmatory factor analysis was further conducted to validate the framework of bias in CPDR. Findings: Four types of bias were identified as the constructs that underlie biased behaviors in CPDR. These four biases were included in the bias framework proposed: preconception, self-affirmation, optimism and interest-oriented. The potency of these types of bias was also evaluated. Practical implications: First, the findings inform that the existence of bias in CPDR is real. Early detection allows management to intervene and steer CPDR team back to rational courses. Second, this study suggests optimizing CPDR procedures to diminish the chance of bias occurring. Originality/value: Bias is almost an uncharted area in CPDR. The study fills this research gap by conceptualizing the underlying constructs of biased behaviors. The findings inform construction professionals of the likelihood of practicing biased behaviors in CPDR. Repeated dispute decisions in the commonly used multi-tiered dispute resolution process would enable the creeping in of biases.